Node assignment problem in Bayesian networks - Polanska, Joanna; Damian, Borys; Polanski, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the problem of searching for the best assignments of random variables to nodes in a Bayesian network (BN) with a given topology. Likelihood functions for the studied BNs are formulated, methods for their maximization are described and, finally, the results of a study concerning the reliability of revealing BNs' roles are reported. The results of BN node assignments can be applied to problems of the analysis of gene expression profiles.
Keywords: biostatistics; Bayesian networks; maximum likelihood; confidence intervals